Cues for Perceived Pitch Register - Rietveld, T.; Vermillion Peirce, Patricia (Karger, 2004)
The aim of this experiment was to assess empirically listeners’ behaviour in characterising pitch contours with the label pitch register. The motivation for this assessment was initiated by the conflicting use of the term register in speech science and intonology. The findings reported here indicate that pitch register would more appropriately be associated with the position of the low pitch targets and the mean value of the tonal contour. In addition, the importance of the reference frequency (the lowest F₀ of a speaker) and the distance between H and L targets have been found to be weaker than previously assumed.